2015
DOI: 10.1002/stem.2118
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide-cGMP-PKG Pathway Acts on Orai1 to Inhibit the Hypertrophy of Human Embryonic Stem Cell-Derived Cardiomyocytes

Abstract: Cardiac hypertrophy is an abnormal enlargement of heart muscle. It frequently results in congestive heart failure, which is a leading cause of human death. Previous studies demonstrated that the nitric oxide (NO), cyclic GMP (cGMP), and protein kinase G (PKG) signaling pathway can inhibit cardiac hypertrophy and thus improve cardiac function. However, the underlying mechanisms are not fully understood. Here, based on the human embryonic stem cell-derived cardiomyocyte (hESC-CM) model system, we showed that Ora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 37 publications
(89 reference statements)
2
36
0
Order By: Relevance
“…The molecular determinants of SOCE include STIM1 and Orai1, in which STIM1 serves as a Ca 2+ sensor in sarco/endoplasmic reticulum whereas Orai1 functions as the pore-forming subunit for Ca 2+ permeation. Previous studies from us and others presented the data consistent with the hypothesis that SOCE and its molecular determinants STIM1 and Orai1 can promote hypertrophy in rat neonatal cardiomyocytes, adult cardiomyocytes and embryonic stem-cell derived cardiomyocytes (Hunton et al, 2002; Voelkers et al, 2010; Hulot et al, 2011; Luo et al, 2012; Wang et al, 2015). …”
Section: Introductionsupporting
confidence: 85%
See 3 more Smart Citations
“…The molecular determinants of SOCE include STIM1 and Orai1, in which STIM1 serves as a Ca 2+ sensor in sarco/endoplasmic reticulum whereas Orai1 functions as the pore-forming subunit for Ca 2+ permeation. Previous studies from us and others presented the data consistent with the hypothesis that SOCE and its molecular determinants STIM1 and Orai1 can promote hypertrophy in rat neonatal cardiomyocytes, adult cardiomyocytes and embryonic stem-cell derived cardiomyocytes (Hunton et al, 2002; Voelkers et al, 2010; Hulot et al, 2011; Luo et al, 2012; Wang et al, 2015). …”
Section: Introductionsupporting
confidence: 85%
“…Previous reports suggest that SOCE is an important immediate signal that contribute to agonist-induced cardiac hypertrophy (Hunton et al, 2002; Voelkers et al, 2010; Hulot et al, 2011; Luo et al, 2012; Wang et al, 2015). This was confirmed in the present study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Orai1 N-terminal intracellular region contains several phosphorylation sites. Ser-27 and -30 are the main phosphorylation sites targeted by PKCβ1 [20], while Ser-34 was found to be a target of protein kinase G (PKG) [36] and, more recently, Zhang and coworkers revealed that Ser-34 is also a PKA phosphorylation site [21]. Phosphorylation of Orai1 at any of these serine residues was demonstrated to result in Orai1 channel inactivation and reduction of Ca 2+ influx.…”
Section: Discussionmentioning
confidence: 99%